Don Juan O'Brien : An Irish adventurer in nineteenth-century South America - Fanning, Tim (Book collections on Project MUSE., 2020)
"This is the first comprehensive study of John Thomond O'Brien, one of the most significant Irish-born figures in the history of modern South America. Born in Baltinglass, County Wicklow, in the late eighteenth-century, O'Brien emigrated to Buenos Aires in the second decade of the nineteenth century, hoping to profit from the burgeoning trade in textiles between Britain and Ireland and the River Plate. In 1813, in Buenos Aires, he enlisted as a cavalry officer in the armies fighting against Spanish rule. His actions on the battlefield, which contributed to the achievement of independence in Argentina, Chile, Peru and Uruguay, and his close acquaintance with the two most famous generals of the war, Jose de San Martín and Simón Bolívar, brought him renown in South America and Europe. O'Brien criss-crossed South America during his colourful post-war career, spending time in Chile, Argentina, Bolivia, Peru, Brazil and Uruguay. In the 1820s, he promoted Irish emigration to Argentina, launched the highest sailing ship in the world on Lake Titicaca and led the campaign of support for O'Connell and Catholic Emancipation among the Irish in Buenos Aires. In the 1830s, he explored the Amazon for gold and was imprisoned in Buenos Aires by the dictator Juan Manuel de Rosas. In the 1840s, he represented the Montevidean government in London and Paris. During the last decade of his life, before his death in 1861, he campaigned to have monuments erected across South America to the leaders of the independence campaign. O'Brien's compelling story mirrors that of a tumultuous period in Irish and South American history"--